Mirrors of Entrapment and Emancipation Forugh Farrokhzad and Sylvia Plath - Rahimi Bahmany, Leila (Iranian Studies Series, 2015)
Mirrors of Entrapment and Emancipation explores the rich diversity of the meanings associated with the mirror and reflection in literature by women on the basis of the works of the Persian Forugh Farrokhzad (1935-1967) and her American contemporary Sylvia Plath (1932-1963). These two poets astutely employed mirror images for the realization as well as for communication of their turbulent psycho-emotional states to their readers, thereby capturing and conveying the essence of women desperately trapped among the antithetical images of twentieth-century womanhood.